The deubiquitinase Otud7b suppresses cone photoreceptor degeneration in mouse models of retinal degenerative diseases - Leah Rie Varner; Taro Chaya; Yamato Maeda; Ryotaro Tsutsumi; Shanshan Zhou; Toshinori Tsujii; Daisuke Okuzaki; Takahisa Furukawa (iScience, 2024)
Summary: Primary and secondary cone photoreceptor death in retinal degenerative diseases, including age-related macular degeneration (AMD) and retinitis pigmentosa (RP), leads to severe visual impairment and blindness. Although the cone photoreceptor protection in retinal degenerative diseases is crucial for maintaining vision, the underlying molecular mechanisms are unclear. Here, we found that the deubiquitinase Otud7b/Cezanne is predominantly expressed in photoreceptor cells in the retina. We analyzed Otud7b−/− mice, which were subjected to light-induced damage, a dry AMD model, or were mated with an RP mouse model, and observed increased cone photoreceptor degeneration. Using RNA-sequencing and bioinformatics analysis followed by a luciferase reporter assay, we found that Otud7b downregulates NF-κB activity. Furthermore, inhibition of NF-κB attenuated cone photoreceptor degeneration in the light-exposed Otud7b−/− retina and stress-induced neuronal cell death resulting from Otud7b deficiency. Together, our findings suggest that Otud7b protects cone photoreceptors in retinal degenerative diseases by modulating NF-κB activity.